2018
DOI: 10.2298/fil1815441c
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on n-normal operators

Abstract: Let T be a bounded linear operator on a complex Hilbert space and n, m ∈ N. Then T is said to be n-normal if T * T n = T n T * and (n, m)-normal if T * m T n = T n T * m . In this paper, we study several properties of n-normal, (n, m)-normal operators. In particular, we prove that if T is 2-normal with σ(T) (−σ(T)) ⊂ {0}, then T is polarloid. Moreover, we study subscalarity of n-normal operators. Also, we prove that if T is (n, m)-normal, then T is decomposable and Weyl's theorem holds for f (T), where f is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Proof. If the range T k (H) is dense, then T is an (n, m)-power normal operator and the theorem holds by Theorem 3.6 in [5]. Assume that T k (H) ̸ = H. Let…”
Section: Definition 228 ([18]) Let T ∈ B(h)mentioning
confidence: 99%
See 3 more Smart Citations
“…Proof. If the range T k (H) is dense, then T is an (n, m)-power normal operator and the theorem holds by Theorem 3.6 in [5]. Assume that T k (H) ̸ = H. Let…”
Section: Definition 228 ([18]) Let T ∈ B(h)mentioning
confidence: 99%
“…Following [5,Corollary 4.3], it was observed that if T ∈ B(H) is (n, m)-power normal, then T is isoloid and polaroid. Corollary 2.30.…”
Section: Definition 228 ([18]) Let T ∈ B(h)mentioning
confidence: 99%
See 2 more Smart Citations
“…In [4][5][6], the authors have studied spectral properties of n-normal operator, that is, an operator T such that T n is normal, in the cases that σ(T) (−σ(T)) = ∅ or σ(T) ∩ (−σ(T)) ⊂ {0}. Since an operator T such that T 2 is hyponormal is algebraically hyponormal, T is isoloid and Weyl's Theorem holds.…”
Section: Introductionmentioning
confidence: 99%